Transforming Education Through Deep Learning Design: Integrating Four Key Elements in School Practice - Apriliyana, Nur Pangesti (Molang: Journal Islamic Education, 2025)
This research aims to develop and implement a deep learning-based learning design through a Design-Based Research (DBR) approach in an Indonesian secondary school context. DBR was chosen for its ability to bridge between pedagogical theory and classroom practice through a reflective and collaborative design cycle. This study was conducted at MTs Mansyaul Ulum involving core subject teachers, grade VIII students, and the school principal. The primary focus of the study was the simultaneous integration of four elements of deep learning: real-world connections, personalization, collaboration between students, and the use of digital technology. Data were collected through classroom observations, in-depth interviews, teacher reflections, student work, and student perception questionnaires, and then analyzed thematically using an inductive approach. The results showed that contextualized and holistic learning design significantly improved students' engagement, meaning of learning, and development of 21st-century competencies. Connection with the real world strengthens the relevance of the material, while personalization encourages learning autonomy. Collaboration is proven to improve both conceptual understanding and social-emotional skills. Digital technology serves as a medium to expand the space for learning exploration. The resulting learning model makes a theoretical contribution to developing the New Pedagogies for Deep Learning framework and a practical contribution in the form of an adaptive and applicable design for teachers and curriculum developers. This research shows that profound learning-based educational transformation is possible, relevant,, and impactful in the context of education